A Biomechanical Analysis of the Free Throw Shooting Technique in Wheelchair Basketball: A Pilot Study - Nikola Prvulovic; Miljan Hadzovic; Ana Lilic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2022)
The aim of this pilot study is to determine the kinematic elements of the free throw shooting technique among wheelchair basketball players from various classes. Three wheelchair basketball players from the wheelchair basketball club "Nais" took part in the study. The players were classified from IWBF classification 1, 3 and 4.5. All of the participants were right-handed. Free throw shooting recording were made with a fixed camera with a 1920 x 1080р resolution, 30 frames per s, positioned at a height of 1.20 m on the right side of the players facing the basket, at a distance of 7.5 m and 25 cm behind the free throw line. The "Kinovea" video program was used to process the results and the kinematic data for the free throw shooting technique of wheelchair basketball players. The kinematic parameters indicate differences in the performance of the free throw shooting technique among wheelchair basketball players from class 1, 3 and 4.5. A difference in successful throws between the participants from class 1, 3 and 4.5: the angle of ball release 50°, 52° and 47°, velocity of ball release 7.58 m/s, 6.25 m/s and 7.27 m/s, and height of ball release 164.49 cm, 180.71 cm and 190.86 cm, while the temporal parameters and angles of the elbow had the same values. We can conclude that for the successful performance of the free throw shooting technique a basketball player needs to achieve greater height of ball release in the final position.